Maternal high-fat feeding in pregnancy programmes atherosclerotic lesion size in the ApoE*3 Leiden mouse - Tarling, Elizabeth J.; Ryan, K.J.P.; Austin, Ruth Marie; Kugler, Susanne J.; Salter, Andrew M.; Langley-Evans, Simon C.
Periods of rapid growth seen during the early stages of fetal development, including cell proliferation and differentiation, are greatly influenced by the maternal environment. We demonstrate here that over-nutrition, specifically exposure to a high fat diet in utero, programmed the extent of atherosclerosis in the offspring of ApoE*3 Leiden transgenic mice. Pregnant ApoE*3 Leiden mice were fed either a control chow diet (2.8% fat, n=12) or a high-fat, moderate-cholesterol diet (MHF, 19.4% fat, n=12). Dams were fed the chow diet during the suckling period. At 28d postnatal age wild type and ApoE*3 Leiden offspring from chow or MHF-fed mothers were fed either a control chow diet (n=37) or a diet rich in cocoa butter (15%) and cholesterol (0.25%), for 14 weeks to induce atherosclerosis (n=36). Offspring from MHF-fed mothers had 1.9-fold larger atherosclerotic lesions (p<0.001). There was no direct effect of prenatal diet on plasma triglycerides or cholesterol, however transgenic ApoE*3 Leiden offspring displayed raised cholesterol when on an atherogenic diet compared to wild-type controls (p=0.031). Lesion size was correlated with plasma lipid parameters after adjustment for genotype, maternal diet and postnatal diet (R2=0.563, p<0.001). ApoE*3 Leiden mothers fed a MHF diet developed hypercholesterolemia (plasma cholesterol 2-fold higher than in chow fed mothers, p=0.011). The data strongly suggest that maternal hypercholesterolaemia programmes later susceptibility to atherosclerosis. This is consistent with previous observations in humans and animal models.